Exchange Complex Composition in Mediterranean Ultisols Under Various Types of Vegetation and Soil Uses - Mariscal-Sancho, Ignacio; Peregrina, Fernando; Mendiola, Maria A.; Santano, Jesus; Espejo, Rafael (SOIL SCIENCE, 2009)
We studied the dynamics of texture, bulk density, exchangeable bases, acidity, and aluminum in the uppermost Surface 50 con of Mediterranean Ultisols under natural vegetation at variable degradation stages and tinder different soil uses in the Canamero's rana formation (southwest Spain). The areas studied included a cork oak grove (the climax vegetation in the area), a field densely covered by Cistus ladaniferus L., a field with 55% covered by Cistus crispus L. and C. ladaniferus, a field with 10% covered by bushes of the same type as the previous one, and a field with grass and occasional Cistus bushes. All of these fields with bushes were extensively cultivated with rye (Secale. cereale L.) and then abandoned 45, 35, 12, and 6 years, respectively, before the study. Finally, we selected an olive grove that had been under continuous tillage for the previous 65 years. The total organic matter content decreased, starting from the virgin soil, under cork oaks, to the most heavily degraded soil (that under olive trees), whereas the bulk density increased. The total contents of exchangeable Ca, Mg, Na, and K significantly decreased in the same trend as organic matter. In contrast, the amount of aluminum extracted by 1N KCl, Al(K), remained essentially constant or even increased with increasing soil degradation. This resulted in a markedly decreased Ca/Al(K) ratio in the topmost 5 cm of soil, which had a strong adverse effect on crop productivity and natural plant recovery after the soils were abandoned.
The following values have no corresponding Zotero field: pub-location: 530 WALNUT ST, PHILADELPHIA, PA 19106-3621 USA publisher: LIPPINCOTT WILLIAMS & WILKINS
Keywords: organic carbon; Soil degradation; soil quality; storage bases

Exchange Complex Composition in Mediterranean Ultisols Under Various Types of Vegetation and Soil Uses - Mariscal-Sancho, Ignacio; Peregrina, Fernando; Mendiola, Maria A; Santano, Jesus; Espejo, Rafael (SOIL SCIENCE, 2009)
We studied the dynamics of texture, bulk density, exchangeable bases, acidity, and aluminum in the uppermost Surface 50 con of Mediterranean Ultisols under natural vegetation at variable degradation stages and tinder different soil uses in the Canamero's rana formation (southwest Spain). The areas studied included a cork oak grove (the climax vegetation in the area), a field densely covered by Cistus ladaniferus L., a field with 55% covered by Cistus crispus L. and C. ladaniferus, a field with 10% covered by bushes of the same type as the previous one, and a field with grass and occasional Cistus bushes. All of these fields with bushes were extensively cultivated with rye (Secale. cereale L.) and then abandoned 45, 35, 12, and 6 years, respectively, before the study. Finally, we selected an olive grove that had been under continuous tillage for the previous 65 years. The total organic matter content decreased, starting from the virgin soil, under cork oaks, to the most heavily degraded soil (that under olive trees), whereas the bulk density increased. The total contents of exchangeable Ca, Mg, Na, and K significantly decreased in the same trend as organic matter. In contrast, the amount of aluminum extracted by 1N KCl, Al(K), remained essentially constant or even increased with increasing soil degradation. This resulted in a markedly decreased Ca/Al(K) ratio in the topmost 5 cm of soil, which had a strong adverse effect on crop productivity and natural plant recovery after the soils were abandoned.
Keywords: organic carbon; Soil degradation; soil quality; storage bases